Biomolecular basis of matrix metallo proteinase-9 activity - Swetha R.; Gayen C.; Kumar D.; Singh T.D.; Modi G.; Singh S.K. (My University, 2025)
Matrix metalloproteinases (MMPs) are structurally related endopeptidases. They are also known as metzincins due to their interaction with zinc ion of the conserved methionine (Met) at the active site. MMPs play an important role in physiological and signaling processes of wound healing, bone resorption and angiogenesis. The structure of MMPs consists of signal peptide, propeptide, catalytic domain, hinge region and hemopexin-like domain. MMP-9 shares high structural and functional similarities with MMP-2, therefore designing selective MMP-9 inhibitors (MMPIs) is challenging. The selectivity can be achieved by targeting S2 subsite of MMP-9 that is having difference with MMP-2. Further, targeting its exosite and protein disulfide isomerase may also provide selective MMPIs. The review highlights the molecular features and basis of MMP-9 enzyme action. The MMPIs reported in the recent years have also been included. © 2018 2018 Newlands Press.